2021
DOI: 10.1002/pbc.28941
|View full text |Cite
|
Sign up to set email alerts
|

Second tumor risk in children treated with proton therapy

Abstract: Background: Out-of-field neutron dissemination during double-scattered proton therapy has raised concerns of increased second malignancies, disproportionally affecting pediatric patients due to the proportion of body exposed to scatter dose and inherent radiosensitivity of developing tissue. We sought to provide empiric data on the incidence of early second tumors. Methods: Between 2006 and 2019, 1713 consecutive children underwent doublescattered proton therapy. Median age at treatment was 9.1 years; 371 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
3
21
2
Order By: Relevance
“…30,31 Younger age is a known risk factor for radiation sensitivity and second cancer development, which was supported by other analyses including the recent study on subsequent neoplasm risk after proton beam RT. 20 This association was not clear in our data, as 9% of the 90 patients aged ≤5 years at IMRT developed a second cancer. Interestingly, of the six hematologic malignancies, two patients were ≤5 years of age at time of IMRT, one of whom developed AML/MDS <5 years after IMRT.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…30,31 Younger age is a known risk factor for radiation sensitivity and second cancer development, which was supported by other analyses including the recent study on subsequent neoplasm risk after proton beam RT. 20 This association was not clear in our data, as 9% of the 90 patients aged ≤5 years at IMRT developed a second cancer. Interestingly, of the six hematologic malignancies, two patients were ≤5 years of age at time of IMRT, one of whom developed AML/MDS <5 years after IMRT.…”
Section: Discussioncontrasting
confidence: 58%
“…19 To address this question, a recent study published reported second cancer risks among 1713 children treated with double-scattered proton therapy with a median of 3.3 years of follow-up. 20 While their study differed from our report by including both benign and malignant tumors, as well as including patients with less than 5 years of follow-up, they do report results on a subset of 549 patients with at least 5 years of follow-up. In this subset, with a median 7.1 years of follow-up, the 10-year cumulative incidence of any second solid neoplasm (benign or malignant) was 2.3%, which is less than our preliminary report (3.3%), leading to their conclusion that proton beam RT does not seem to increase the risk of second cancers and may in fact reduce the risk as seen in adults.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Unlike our study, that study treated different types of tumors, including those outside the brain, with different RT fields and doses, with Cancer October 15, 2021 or without CT, and excluded children with tumor predisposition syndromes. 20 In 1 study from the St Jude-Washington University Pediatric Cancer Genome Project, 8.5% of children and adolescents had germline mutations identified in cancer predisposing genes. 21 We did not have any patients with a known tumor predisposition syndrome; however, as the Pediatric Cancer Genome Project reported, some of our patients probably have undetected mutations in cancer predisposing genes.…”
Section: Discussionmentioning
confidence: 99%
“…Proton radiation therapy (PR) is well established in the treatment of pediatric primary central nervous system (CNS) malignancies, with known dosimetric advantages compared with traditional photon radiation and increasing retrospective evidence showing reduced risk of late effects including cognitive decline and secondary malignancy. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Prior publications have reported on national PR practice patterns, which were notable for racial and sociodemographic disparities in the application of proton therapy. 19 In the years since the most recent national level database analysis was published, the number of available proton therapy centers increased by about 200%.…”
Section: Introductionmentioning
confidence: 99%